The role of transformational leadership In improving muslim students entrepreneurship - et. al., Maemunah Sa’diyah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Buya K.H. Husen Harahap has succeeded in building and improving the entrepreneurship based Islamic boarding school which is still rare to find Indonesia, especially West-Java. This study aims to understand the role of transformational leadership applied by Buya K.H. Husen Harahap in cultivating Muslim students’ entrepreneurship. Qualitative data collection method in particular to the in-depth interview was conducted. The school management staffs were interviewed to explore the strategies applied in managing the school. The main characteristic of the transformational leadership applied is the transformation of the unproductive land into the productive one through seven strategies which are: (1) creating vision and mission, (2) stimulating students’ leadership and entrepreneurship, (3) building the cooperation unit, mineral water company, and fruit farms, (4) formulating the entrepreneurship oriented curriculum, (5) creating the vegetables and fruits garden, (6) engaging the students in practical business activity, and (7) providing the role models to the students and teachers